Bimetallic MOF-derived CNTs-grafted carbon nanocages as sulfur host for high-performance lithium–sulfur batteries. (20th July 2020) - Zhou, Fan; Qiao, Zhensong; Zhang, Yinggan; Xu, Wanjie; Zheng, Hongfei; Xie, Qingshui; Luo, Qing; Wang, Laisen; Qu, Baihua; Peng, Dong-Liang
Abstract: Carbon materials, especially those with hollow structure, have gained considerable attention as the host materials for sulfur in Li–S batteries. Herein, the nanocages consisting of carbon nanotubes (CNTs) and hierarchically porous carbon (CNT-NC@GC) are synthesized using bimetallic core-shell metal-organic frameworks as precursor. CNTs are in situ introduced onto the inner/outer surface of the nanocages to form a three-dimensional conductive network throughout the entire electrode for the favorable electrolyte penetration and improved electrons/ions transfer. Abundant N-doping and Co nanoparticles decoration in the tips of CNTs or on the surface of GC shells are beneficial to immobilize soluble polysulfides. Moreover, the modified Co nanoparticles possess chemisorption and electrocatalytic activity for sulfur conversion, which can promote redox kinetics of the polysulfides and improve the cycling stability. As a result, the as-prepared CNTs-grafted nitrogen-doped carbon@graphitic carbon nanocages cathode containing 79.2 wt% of sulfur (CNT-NC@GC/S) delivers a high discharge capacity of 743 mA h g −1 after 500 cycles at a current density of 1.0C with a capacity retention of 83.6%. And the cathode with high areal sulfur loading of 4.95 mg cm −2 shows a high areal capacity of 4.01 mA h cm −2 over 100 cycles. Graphical abstract: CNTs-grafted nitrogen-doped carbon@graphitic carbon nanocages with the metallic Co embedded can suppress the shuttle effect by physical and chemical adsorption, and the integrated CNTs conductive network favors the diffusion of electron within the whole electrode and then features high utilization of sulfur. Image 1